Perinatal lung function and invasive antenatal procedures. Issue 2 (February 1997) - Yüksel, B; Greenough, A; Naik, S; Cheeseman, P; Nicolaides, K H
Abstract : BACKGROUND: Second trimester amniocentesis has been associated with an excess of perinatal lung function abnormalities. Early amniocentesis might have a similar adverse effect, as could other invasive investigations carried out in the first trimester. METHODS: Plethysmographic measurements of thoracic gas volume (TGV) and airway resistance (Raw), from which specific conductance (sGaw) was calculated, were made in the perinatal period in non-sedated infants. In addition, functional residual capacity (FRC) was measured using a helium gas dilution technique. Measurements were made in 47 infants whose mothers had undergone early amniocentesis, 19 whose mothers had undergone chorion villus sampling, and 25 controls whose mothers had undergone no invasive antenatal procedures. RESULTS: The infants of mothers who had undergone early amniocentesis had higher TGV (95% CI -6.3 to 1.1 ml/kg) and Raw values (95% CI -10.68 to -5.23 cm H2O/l/s) and lower sGaw (0.11 to 0.84 l/cm H2O.s) and FRC (-5.17 to - 0.87 ml/kg) values than the controls. Infants whose mothers had undergone chorion villus sampling also differed significantly from the controls with higher Raw (-7.59 to -1.99 cm H2O/l/s) and lower sGaw values (0.11 to 0.24 l/cm H2O.s), and had lower Raw values than those in the early amniocentesis group (not significant). Logistic regression analysis, taking into account possible risk factors for abnormal lung function, showed that the procedures performed in the first trimester were independently associated with a high airways resistance. CONCLUSION: These results suggest that invasive procedures performed in the first trimester of pregnancy have an adverse effect on perinatal lung function.